Growth performance of ten irrigated rice (Oryza sativa L.) varieties under agroecosystem conditions in Central Tapanuli Regency - Siti Nurhalizah Tambunan; Nilahayati Nilahayati; Laila Nazirah; Nasruddin Nasruddin; Jamidi Jamidi (Agrium, 2026)
Rice (Oryza sativa L.) is the primary staple food crop in Indonesia and plays an essential role in supporting food security. The cultivation of rice varieties with poor adaptability often leads to reduced productivity. Therefore, evaluating superior rice varieties under specific agroecosystem conditions is necessary to identify those with strong growth performance and adaptability. This study aimed to evaluate the growth performance of 10 irrigated rice varieties grown under agroecosystem conditions in Central Tapanuli Regency. The experiment was conducted using a non-factorial Randomized Complete Block Design (RCBD) with three replications. Ten rice varieties were evaluated: Inpari 30, Inpari 32, Inpari 42, Inpari 43, Ciherang, Mekongga, Cigeulis, Padjadjaran, Cakrabuana, and Siporang. Observed variables included plant height, number of tillers, leaf area, and flowering age. The results indicated that rice variety had no significant effect on plant height at 20, 40, and 60 days after transplanting (DAT). However, significant differences were observed in the number of tillers at 60 DAT, leaf area at all observation periods, and flowering age. The Siporang variety exhibited superior vegetative growth, producing the tallest plants (116.16 cm) and the largest leaf area (71.00 cm²) at 60 DAT. Meanwhile, Inpari 43 produced the highest number of tillers (48.58 tillers hill⁻¹). These findings suggest that Siporang and Inpari 43 exhibited superior growth performance and may be considered promising varieties for cultivation under the agroecosystem conditions of Central Tapanuli Regency.